Menu engineering mechanism for restauranthousehold establishments that serve the organized groups of consumers in recreational regions - Sabadosh, Ganna Oleksandrіvna (Національний технічний університет "Харківський політехнічний інститут", 2019)
Restaurant household establishments in health and tourist centers, children camps are obliged to implement fully food rations in the menu engineering during the term of staying the contingent of consumers according to the requirements of physical needs. Therefore, during the menu engineering is selected a certain menu variety, calculated the cost of raw materials for its implementation and certainly compared with established standards. This publication is designed to provide accurate and authoritative information inregard to the subject matter covered. This article has been developed for use in courses introducing food, beverage, and labor cost controls to students preparing for careers in food and beverage management as well as hotels and other enterprises where this knowledge is necessary: menu engineering is the study of the profitability and popularity of menu items and how these two factors influence the placement of these items on a menu.

Підприємства ресторанного господарства при санаторіях, туристичних комплексах, дитячих таборах, зобов'язані при складанні меню дотримуватися фізіологічних норм в харчових раціонах на протязі терміну перебування груп споживачів, згідно вимог до фізіологічних потреб людини. Згідно контингенту, розроблені відповідні раціону харчування. Тому, при складанні меню підбирається потрібний варіант, розраховуються витрати сировини на його реалізацію, та обов'язково проводиться порівняння зі встановленими нормами.
Механізм розробки меню для підприємств ресторанного господарства, які обслуговують в рекреаційних регіонах організовані групи споживачів
Keywords: principle variables; structuring principle; principle of adaptation; принцип варіабельності; принцип структуризації; принцип адаптації